Implementation of Modeling and Reinforcement Process from Lecturers in Forming Anti-Corruption Attitide of Student Activist: A Study at University of Muhammadiyah Malang, Indonesia - Sukmana, Oman; Agustino, Hutri; Widodo, Eko Rizki Purwo (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine how the implementation of the modeling and reinforcement processes of lecturers in the formation of anti-corruption attitudes towards student activists. Research uses a qualitative approach and descriptive-qualitative type of research. The research subjects were 15 student activists of the Social Welfare Study Program. Data collection techniques were carried out through interviews and questionnaires, while data analysis techniques were carried out through the process of data reduction, data presentation, and drawing conclusions (verification). The results of the research show that the form of the modeling process implemented by lecturers is done by giving examples of behavior such as: transparency of grades, lectures on time, accountability of lecture material, democratic learning processes, transparency in the allocation of funds for student activities, disciplined, and honest. While the form of implementation of the reinforcement process is done through verbal and no-verbal forms, such as: reprimanding, reminding, sanctioning, giving bonuses to academic grades of the course. The implementation of the modeling and reinforcement process by lecturers has an impact on anti-corruption attitudes on students. The implication of the results of this study is that the formation of anti-corruption attitudes on students can be done by lecturers through the implementation of Cognitive-Mediatonal Theory. The results of the questionnaire data analysis showed that the percentage of the average score of anti-corruption attitudes among student activists in the category was very high. This means that student activists have a positive attitude towards anti-corruption behavior.